Peran Ibu Rumah Tangga dalam Menopang Ekonomi di Masa Krisis - Sofiyatun Hasanah; Lisa Dwi Aprillia; Yunisa Aini Fatmala; Bramas Tri Angga Putra; Muhammad Ilham (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
Pandemi Covid-19 has a big impact on various aspects of life, including the household economy in Indonesia. In the midst of these conditions, the role of the mother as the family's economic pillar is becoming increasingly prominent. This study discusses the real contribution of mothers in maintaining household economic stability, especially through informal economic activities, micro businesses, and digitalization utilization. This phenomenon shows the presence of an added-worker effect, where housewives are involved in economic activity in response to the decline in family income. Although dominant in the informal sector with minimal protection, mothers show high levels of resilience and creativity in carrying out their dual roles. This study also highlighted the challenges faced, such as social norms that still place women in subordinate positions as well as low recognition of domestic work. Therefore, there is a need for policies that support and protect the role of mothers as important agents in the recovery and development of the national economy.